Reengaging in agricultural water management : challenges and options. - World Bank. (Washington, DC : World Bank, 2006)
The main message of thia book is that the irrigation and drainage sector should not continue to be dealt with as a standalone sector, but should be integrated into a broader perspective, one that embraces the objectives of productivity growth, poverty reduction, natural resources management and environmental protection.
Includes bibliographical references (p. 201-209) and index.
oif 16/09/15
Loan
Keywords: Water-supply, Agricultural -- Management